Mutations in GFPT1-related congenital myasthenic syndromes are associated with synaptic morphological defects and underlie a tubular aggregate myopathy with synaptopathy - Bauche, Stephanie; Vellieux, Geoffroy; Sternberg, Damien; Fontenille, Marie-Josephine; De Bruyckere, Elodie; Davoine, Claire-Sophie; Brochier, Guy; Messeant, Julien; Wolf, Lucie; Fardeau, Michel; Lacene, Emmanuelle; Romero, Norma; et al. (Journal of Neurology, 2017)
Mutations in GFPT1 (glutamine-fructose-6-phosphate transaminase 1), a gene encoding an enzyme involved in glycosylation of ubiquitous proteins, cause a limb-girdle congenital myasthenic syndrome (LG-CMS) with tubular aggregates (TAs) characterized predominantly by affection of the proximal skeletal muscles and presence of highly organized and remodeled sarcoplasmic tubules in patients' muscle biopsies. We report here the first long-term clinical follow-up of 11 French individuals suffering from LG-CMS with TAs due to GFPT1 mutations, of which nine are new. Our retrospective clinical evaluation stresses an evolution toward a myopathic weakness that occurs concomitantly to ineffectiveness of usual CMS treatments. Analysis of neuromuscular biopsies from three unrelated individuals demonstrates that the maintenance of neuromuscular junctions (NMJs) is dramatically impaired with loss of post-synaptic junctional folds and evidence of denervation-reinnervation processes affecting the three main NMJ components. Moreover, molecular analyses of the human muscle biopsies confirm glycosylation defects of proteins with reduced O-glycosylation and show reduced sialylation of transmembrane proteins in extra-junctional area. Altogether, these results pave the way for understanding the etiology of this rare neuromuscular disorder that may be considered as a "tubular aggregates myopathy with synaptopathy".
EVALuna2:36572